A neural signature for gastrointestinal symptoms in depression: insula-gastric connectivity predicts symptom severity - Qi, Li; Zhang, Ting; Pan, Xiaomin; Gao, Zhishun; Li, Jin; Yu, Yue; Wang, Wenjia; Wei, Qiang; Yang, Jin-Ying; Wang, Kai; Bai, Tongjian; Li, Qianqian (Frontiers in Psychiatry, 2025)
BackgroundGastrointestinal (GI) symptoms are a common and burdensome dimension of major depressive disorder (MDD), yet their neurobiological underpinnings are poorly understood. It is unclear how the brain’s processing of visceral signals relates to the subjective experience of GI distress in depression. We aimed to identify a neural substrate for GI symptoms by examining functional connectivity (FC) between the insula and a network defined by gastric rhythms.MethodsWe first identified a gastric-related seed in the posterior insula (GD-pINS) using a large normative dataset of 652 healthy adults. Subsequently, 100 MDD patients—stratified into groups with (GD; n=58) and without (NGD; n=42) GI symptoms—and 80 healthy controls (HCs) were recruited. Using resting-state fMRI, we analyzed FC between the GD-pINS and the gastric network (GN). Group differences, clinical correlations, and the utility of FC features for patient classification via a support vector machine (SVM) were assessed.ResultsCompared to HCs, MDD patients as a whole showed reduced GD-pINS to GN connectivity. Paradoxically, GD patients exhibited relatively stronger connectivity than NGD patients. This symptom-specific enhancement was driven by pathways connecting the posterior insula to the secondary somatosensory cortex (SII). The strength of this insula-SII connection was positively correlated with GI symptom severity. An SVM classifier using these connectivity features distinguished between GD and NGD patients with high accuracy (AUC = 0.82).ConclusionsOur findings reveal a distinct neural signature for GI distress in depression, characterized by aberrant connectivity within an insula-somatosensory circuit. This circuit, which shows relative enhancement in symptomatic patients against a backdrop of globally reduced connectivity, may reflect a mechanism of somatosensory amplification. It represents a potential biomarker for patient stratification and a novel target for therapeutic intervention.